Marginal Cost Pricing Under Bounded Marginal Returns - Vohra, Rajiv (Econometrica, 1992)
Most of the available results on the existence of marginal cost pricing equilibrium are unsatisfactory in that they make a survival assumption that is stated as a condition on the production equilibria of the economy. The primary objective of this paper is to provide a relatively elementary existence result that replaces such an assumption with one on the primitive data of the economy. The author's main assumption is that no firm faces unbounded increasing returns in the sense that if it uses some input then the rate at which this input can be substituted into an output is finite. Copyright 1992 by The Econometric Society.